The chemistry and biological activities of N-acetylcysteine - Samuni, Yuval; Goldstein, Sara; Dean, Olivia M.; Berk, Michael (Biochimica et biophysica acta, 2013)
N-acetylcysteine (NAC) has been in clinical practice for several decades. It has been used as a mucolytic agent and for the treatment of numerous disorders including paracetamol intoxication, doxorubicin cardiotoxicity, ischemia–reperfusion cardiac injury, acute respiratory distress syndrome, bronchitis, chemotherapy-induced toxicity, HIV/AIDS, heavy metal toxicity and psychiatric disorders. The mechanisms underlying the therapeutic and clinical applications of NAC are complex and still unclear. The present review is focused on the chemistry of NAC and its interactions and functions at the organ, tissue and cellular levels in an attempt to bridge the gap between its recognized biological activities and chemistry. The antioxidative activity of NAC as of other thiols can be attributed to its fast reactions with OH, NO2, CO3− and thiyl radicals as well as to restitution of impaired targets in vital cellular components. NAC reacts relatively slowly with superoxide, hydrogen-peroxide and peroxynitrite, which cast some doubt on the importance of these reactions under physiological conditions. The uniqueness of NAC is most probably due to efficient reduction of disulfide bonds in proteins thus altering their structures and disrupting their ligand bonding, competition with larger reducing molecules in sterically less accessible spaces, and serving as a precursor of cysteine for GSH synthesis. The outlined reactions only partially explain the diverse biological effects of NAC, and further studies are required for determining its ability to cross the cell membrane and the blood–brain barrier as well as elucidating its reactions with components of cell signaling pathways. [Display omitted] •The chemistry of N-acetylcysteine (NAC) is reviewed.•NAC can detoxify oxidizing radicals and bind redox-active metal ions.•NAC is a precursor of cysteine thus maintaining GSH intracellular levels.•NAC can efficiently reduce disulfide bonds in proteins thus altering their structures.•Not all mechanisms underlying the biological activities of NAC are already clear.